The adverse effects on employees of the unbridled exercise of certain management prerogatives - Almario Chan, Jan Franz Norbert Joselito (Philippine Law Journal, 2019)
There are certain rights and prerogatives belonging to employers that are not found in the Labor Code or in any other laws but are well-recognized in jurisprudence. Their significance is highlighted by the fact that a constantly growing number of cases involving the issue of the validity of the exercise by employers of their management rights and prerogatives have reached the Supreme Court.